2007
DOI: 10.1111/j.1463-1326.2007.00785.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of β‐cell mass and function in the Göttingen minipig

Abstract: Increased knowledge about b-cell mass and function is important for our understanding of the pathophysiology of type 2 diabetes (T2DM). The relationship between the two is difficult to study in humans, whereas animal models allow studies of consequences of, for example, reduction of b-cell mass and induction of obesity and procurement of the pancreas for histological examination. An overview of results obtained in the Gö ttingen minipig in relation to b-cell function, and mass is provided here. Effects of a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…In severely obese Göttingen minipigs (w100 kg), beta-cell mass was increased by w2-fold. However, the relative beta-cell mass was significantly reduced in the obese group, indicating that a normal beta-cell mass-to-body weight ratio could not be sustained in response to the largely increased body weight [138]. Similarly, a 1.3-fold increase in beta-cell volume fraction was observed in adult, obese baboons [139].…”
Section: Pancreasmentioning
confidence: 86%
“…In severely obese Göttingen minipigs (w100 kg), beta-cell mass was increased by w2-fold. However, the relative beta-cell mass was significantly reduced in the obese group, indicating that a normal beta-cell mass-to-body weight ratio could not be sustained in response to the largely increased body weight [138]. Similarly, a 1.3-fold increase in beta-cell volume fraction was observed in adult, obese baboons [139].…”
Section: Pancreasmentioning
confidence: 86%
“…An increasing amount of data suggest that neogenesis and beta cell proliferation are distinct, but not mutually exclusive, pathways executed during pregnancy. The relative contributions may depend on species . Observations by Butler et al.…”
Section: Adaptation Of Beta Cells To Pregnancymentioning
confidence: 99%
“…It should be noted that not all rodent models of β-cell growth show neogenesis: no increases in islet number were seen in pregnancy in mice (12) or in adult ob/ob mice compared with ob /+ controls (13); both of these studies showed increased β-cell mass with larger islets, supporting replication as the mechanism of expansion. One must be aware of possible species differences, as illustrated by neogenesis not being reported in adult mice fed a high-fat diet but reported in adult pigs that became obese after ad libitum feeding for 1–2 years (14). Additionally, in contrast to the data from rodents, the adaptive increase in β-cells during pregnancy in humans is accompanied by decreased mean islet size, increased number of β-cells in “apparently new small islets” with no change in β-cell size, replication, or apoptosis frequency (15).…”
Section: β-Cell Expansion In Normal Growthmentioning
confidence: 99%